(untitled) (Fiep Bulletin - online, 2011)
This study aimed to identify the major injuries incurred in soccer, futsal, and seek to determine the apparent relation to the two modes as they have similar characteristics in the physical contest. The study is quantitative trait, where the sample was composed of 15 players of the Club de Campo Grande Cene, professional category, and that counts in his squad of athletes aged 20 to 32 years. Futsal in 15 athletes participated in the study, aged between 18 and 37 years representing the team futsal UCDB. All the athletes signed TLCE (Free Consent Term clarification) becoming aware of the important role they were developing for the research. A questionnaire was used which involved issues related to time to practice football or soccer, history of injury, recovery time, type of injury, types of chronic pain, discomfort and impairment caused by injuries. the results it was possible to identify more members injured in football is the anterior thigh 55%, ie, the highest index of muscle damage is, in soccer the highest incidences of injury is the twist at 90%, ie osteo-articular lesion. For professionals who work with the football and soccer this study may point to beware that the incidence of injuries so they can minimize the most of some types of injuries very common in these modalities.